Potenciais turísticos no entorno do Teatro Amazonas: caminhos e lugares linguagens artístico-culturais - Silva, Luiz Carlos Braga (2021)
The current dissertation presents the considerations of a research focused on the Semiotics of Tourism, with a focus on Interdisciplinarity. Linked to this line of research, an exploratory and interpretative analysis of the context of artistic-cultural languages present in the cultural spaces surrounding the Teatro Amazonas in the Centro’s neighborhood in Manaus is analyzed as an offer for local tourist practices. The respective cultural spaces chosen for this research were: "Ateliê 23", "Casarão de Idéias", "Galeria do Largo", "Palácio da Justiça", and "Casa das Artes". These places are home to different aspects that varies between the arts of theater, visual arts, cinema, literature and many others, different perspectives of a living and inhabited historical center formed by the arts that represent a different angle of the daily life of the society of Manaus and Amazonas. In this research, an appropriate interdisciplinarity of Semiotic theories was used, in order to analyze how artistic-cultural languages and the cultural spaces themselves in search of understanding the diversity of the local cultural dynamics, Tourism theories in order to understand new possibilities of studies in the area that involves ways to cover varied offers to visitors, theories of Arts that are thought of in the field of culture frequently, seeking to understand them under tourism studies, theories of Geography with a special understanding of the dynamics present in the territorial spatiality of a cluster. urban Amazon and finally, Cartography theories to map these phenomena for a better visualization of the artistic aspects and their determined occurrences in the historical center of the Amazon capital for a better approach about the problematic presented in this work. The results present as varied cultural dynamics that are commonly excluded from the local tourism sector when they are absent from tourist maps and itineraries around the city. Illustration methods were used to better address the importance of image in the study of Tourism Semiotics and to present more clearly, some of the artistic-cultural languages present in the historic center of Manaus. After the research, it was concluded that there is a great diversity of offers that are not absorbed by the manauara tourist trade that could renew the activities of the tourism field to maintain a greater attention in the urban space of the city, generating income for the local community and knowledge deeper understanding of the visitor with the Amazonian culture and arts.